2014
DOI: 10.4103/1596-3519.134412
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and outcome of surgical management of nasolachrymal duct obstruction in children: A five year review

Abstract: There were 17 patients, 9 males and 8 females (M: F = 1.1: 1). Two patients (11.8%) had bilateral disease and 15 (88.2%) were unilateral. The patients' ages ranged between 2 and 10 years. The commonest presenting features were tearing and discharge. In 14 patients (82%) tearing started from birth though patients presented much later. Congenital NLDO occurred in 82%, and in the remaining 18%, obstruction was caused by depressed nasal fracture. Fifteen patients (88%) had successful outcome of DCR at 1-year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…A Study in Nepal reported the acquired NLDO 63% of cases. Marr and colleagues [10][11][12] in their study reported 92% of patients had congenital NLDO and only 8% acquired cases, which is nearly close to our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A Study in Nepal reported the acquired NLDO 63% of cases. Marr and colleagues [10][11][12] in their study reported 92% of patients had congenital NLDO and only 8% acquired cases, which is nearly close to our study.…”
Section: Discussionsupporting
confidence: 91%
“…Abdu and Salisu [10] reported 88% of success rate of external DCR in children with 1 year post op follow up.…”
Section: Discussionmentioning
confidence: 98%